Determinan Adopsi Sistem Informasi Akuntansi pada UMKM Kota Medan - Wati, Nia; Silalahi, Alistraja Dison; Pratania Putri, Arie (Al-Buhuts, 2023)
This study aims to provide empirical evidence regarding the factors that influence the use of an accounting information system (AIS) in MSMEs in Medan City. This study uses primary data obtained from a questionnaire survey. The type of research used is quantitative, namely analyzing the relationship between one variable and another. The population in this study are several MSME actors who are directly involved in using the accounting information system. The sample used was 66 SMEs. The data analysis used is multiple linear regression. Using the Windows SPSS program version 20 to process all data obtained. The results of this study indicate that the variables of personal technical ability, education and training programs and user involvement have a significant influence on the use of accounting information systems because they are to add insight, knowledge, provide facilities in the form of a reliable system and make it easier for MSME actors to use accounting information systems